EP953 Poor AT and VO2 max recorded during cardiopulmonary exercise testing (CPET) prior to cytoreductive surgery in advanced (Stage 3/4) ovarian cancer (AOC) is associated with suboptimal cytoreduction but does preclude maximum effort cytoreduction. (1st November 2019) - Element, K; Mehrotra, P; Asher, V; Bali, A; Abdul, S; Low, J; Curtis, R; Tou, S; Gomez, D; Phillips, A
Abstract : Introduction/Background: Using CPET pre-operatively to assess functional capacity and help estimate if patients can cope with the physiological stress of major surgery is increasing utilised across many different conditions. No research is currently available on the value CPET can have on predicting outcomes and complications following AOC cytoreductive surgery. Methodology: A retrospective review of all patients who had CPET prior to AOC cytoreductive surgery with evidence of upper abdominal disease on preoperative imaging at the University Hospitals of Derby and Burton (UHDB) between August 2016 and February 2019. Patients were stratified into two groups, based on their anaerobic threshold (AT) (AT <11 and AT ≥11) and maximum VO2 (VO2 <15 and VO2 ≥15). Cytoreduction (Complete (R0), <1 cm (R1) or >1 cm (R2)), surgical complexity, complications within thirty days, length of hospital stay (LOS) and readmissions were assessed. Results: 36 patients were identified. AT showed no relationship with thirty-day complications or death rates. 100% of patients in the AT≥11 group received R0 (n=18, 90%), or R1 (n=2, 10%) cytoreduction, whereas in the AT <11 group, only 68.75% underwent macroscopic resection (R0/R1, p=0.01). Surgical complexity was higher in the AT ≥11 group (p=0.003) and the VO2 ≥15 group (p=0.003). No other correlations were seen between AT or VO2 max and complications, LOS or readmissions. Conclusion: CPET is not an effective tool for determining appropriateness for surgery. No correlation has been found between performance at testing and complication rates. The majority of patients with AT <11 achieved R0/R1 resection despite a higher rate of suboptimal surgery. Discounting patients from cytoreductive surgery based on CPET results alone is not supported by our study, however CPET may have a role in conjunction with other investigations. (eg. echocardiogram, PFT´s), or in selected patients. Disclosure: Nothing to disclose.